The Utilization of the Siginjai Museum as a Local Wisdom-Based History Learning Resource - Alifa Selia Fitri; Adellia Ayu Lestari; Shabrina Arpia; Dewi Rembulan (Greenation Education and Culture Review, 2026)
History education in schools is still dominated by lecture-based methods and the use of textbooks, resulting in low student engagement and a suboptimal understanding of local history and regional cultural values. This study aims to examine the use of the Siginjai Museum as a source of history education based on local wisdom in the modern era. The study employs a qualitative approach using library research (literature review) through an analysis of 20 scholarly articles and various literature sources published between 2020 and 2025, obtained from Google Scholar, Crossref, DOAJ, and Garuda. Data analysis was conducted using content analysis techniques through the stages of data reduction, theme categorization, content interpretation, and conceptual synthesis. The results of the study indicate that the Siginjai Museum has significant potential as a source of contextual history education because it provides a collection of artifacts, cultural relics of the Jambi Malay, and historical evidence relevant to the lives of students. The research findings also indicate that the use of museums can strengthen cultural awareness, enhance understanding of local history, and instill local values such as mutual cooperation, religiosity, consensus-building, and respect for local customs. Furthermore, integrating museums into learning can be achieved through educational visits, project-based learning, artifact observation, and the use of museum digital media that support 21st-century learning. This study also found that the implementation of museum-based learning still faces challenges such as limited facilities, low museum literacy, and a lack of innovation in learning based on local resources. The novelty of this study lies in the analysis of the integration of local wisdom values within the Siginjai Museum’s collection as a source of contextual history learning a topic rarely addressed in previous research. This study is expected to serve as a reference for teachers, schools, and museum administrators in developing history learning that is more interactive, reflective, and rooted in local culture.